Community Empowerment Through Digital Marketing Optimization For Msmes In Kabupaten Tasikmalaya - R. Hozin Abdul Fatah; Siti Amirah Makarim (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2026)
This community service program aims to empower Micro, Small, and Medium Enterprises (MSMEs) in Kabupaten Tasikmalaya by optimizing digital marketing strategies. Kabupaten Tasikmalaya is known for its diverse local products, including embroidery (bordir), mendong handicrafts, and processed foods. However, many MSMEs still face significant challenges in market expansion, primarily due to limited digital literacy and traditional marketing methods. Data from the local Department of Cooperatives and MSMEs indicates that out of over 24,000 registered MSMEs, less than 4% have effectively integrated digital marketing into their business models. This program was conducted over a two-month period (April–May 2026) using a participatory approach, including digital literacy workshops, social media management mentoring, and e-commerce platform integration. The methods employed included initial potential mapping, SWOT analysis, intensive training, and post-implementation monitoring. The results demonstrated a significant increase in the participants' digital competency, with 85% of mentored MSMEs successfully establishing active online storefronts and experiencing an average 15-20% increase in monthly inquiries. This empowerment strategy proves that digital transformation is essential for MSMEs to enhance competitiveness and achieve sustainable economic growth in the digital era.